Peningkatan Penjualan Produk Cinderamata pada UMKM Desa Sawarna Melalui Aplikasi Sitaman Bumi Terintegrasi Batour - Simamora, Muhammad Gifari H; Zakaria, Muhammad Faridzain; Syahrani, Gina; Budi, Rifky Kurniawan Setya; Purnama, Rafi; Sauri, Yayan Sofyan; Azhar, Mochammad Fikry Maulana; Aryanto, Didit; Syaputra, Darmawan Rizky; Fauziah, Nina Syifa; Laksana, Tri Ginanjar (Institut Teknologi Pendidikan Indonesia, 2024)
Sitaman Bumi application is or as it is known today, an innovative software specifically designed to manage the Bayah Dome Geopark in Bayah District, Lebak Regency, Banten Province. It is expected that this software application can make a positive contribution to improving education, management of tourism activities and the economy in developing the potential of the Bayah Dome Geopark. The purpose of implementing this community service is how to increase sales of souvenir products managed by MSMEs in Sawarna Village, the marketing strategy involves utilizing the Batour application as a tool to market these products to visiting tourists. Currently, marketing and promotion of souvenir products in Sawarna Village, especially those carried out by PKK mothers are still conventional. A number of souvenir products managed by PKK women experience difficulties in sales that lead to stock accumulation and financial losses. In overcoming this problem, those involved in empowerment efforts need to provide support and motivation to the community so that they can improve their skills in marketing strategies. This aims to increase sales and expand the market for souvenir products.